2002
DOI: 10.1021/jp020466z
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the aza-Wittig Reactions of X3PNH (X=H and Cl) with Formaldehyde in Gas Phase and in Solution

Abstract: The aza-Wittig reaction of iminophosphoranes (X 3 PdNH, X)H and Cl) with formaldehyde (H 2 CO) was investigated in gas phase and in water using ab initio MP2/6-31G** level of theory and the self-consistent reaction field theory (isodensity polarized continuum model, IPCM). In the gas phase, the aza-Wittig reaction was predicted to be a two-step process with two dipole-dipole complexes, one four-membered ring intermediate and two transition states. The potential energy profiles along the minima energy path in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Moreover, two conformers for the cyclic intermediate are reported. Other authors ,, have made a theoretical study of the aza-Wittig reaction but have reported only geometrical data and energetic barriers. However, the arsa-Wittig reaction is a useful organic reaction for constructing CAs double bonds and in olefination chemistry because of its high stereoselectivity and the mild reaction conditions used, for which no theoretical data have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, two conformers for the cyclic intermediate are reported. Other authors ,, have made a theoretical study of the aza-Wittig reaction but have reported only geometrical data and energetic barriers. However, the arsa-Wittig reaction is a useful organic reaction for constructing CAs double bonds and in olefination chemistry because of its high stereoselectivity and the mild reaction conditions used, for which no theoretical data have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…21 On the basis of a theoretical study, Cossío et al 22 conclude that the reaction corresponds to a formal [2 + 2] cycloaddition. Xue et al 23 gave structural information on the different steps involved in the reaction together with thermodynamic and kinetic properties. The characteristics of the bond in iminopnictoranes and its behavior in the aza-Wittig reactions have been described by Koketsu et al, 24 reporting a zwitterionic bond in NÀpnicogen ylides, although the double-bond character is explained by negative hyperconjugation.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the aza-Wittig reaction between iminophosphoranes with aldehydes, ab initio calculations have shown that these molecular orbitals are involved in a [2+2] cycloaddition leading to a stable intermediate, further evolving into the products containing a double nitrogen–carbon bond . Other calculations for simple iminophosphorane and aldehyde derivatives have been reported in the literature. …”
Section: Introductionmentioning
confidence: 99%
“…1,[6][7][8][9][10][11] Recently, several theoretical studies on the mechanism of the aza-Wittig reaction have been provided. 3,[12][13][14][15] We have provided the first computational report on the mechanism for the phospha-Wittig reaction. 16 However, to the best of our knowledge, this is the first computational report concerning a systematic study of the substitution effect on the mechanism for the arsa-Wittig reaction based on the more sophisticated theory.…”
Section: Introductionmentioning
confidence: 99%